The Influence of Work Motivation and Job Stress on Job Satisfaction of Entry Level Start-Up Employees - Nugroho, Ridho Bayu; Muljono, Pudji; Hidayatilloh, Furqon Syarief (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of work motivation and job stress on job satisfaction among entry-level employees in start-up companies. This phenomenon is particularly relevant given the dynamic nature of start-up work environments and the dominance of Generation Z in the workforce structure. Data were collected through questionnaires administered to 271 respondents working in the start-up sector and analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results indicate that work motivation has a positive and significant effect on job satisfaction, while job stress has a significant negative effect. Simultaneously, both variables contribute significantly to job satisfaction, with an R² value of 0.925. These findings highlight that creating a work environment that fosters motivation while minimizing stress is essential to enhancing job satisfaction, particularly among Generation Z employees. This study provides theoretical implications for the development of human resource management research and practical recommendations for managing employees in competitive and adaptive start-up work environments.